Educational Inspectorate Systems in Comparison: The Chinese System and the Dutch System - Sun, Hechuan; Zheng, Dan (2009)
From six different aspects, the educational inspectorate systems (EIS) in China and in the Netherlands are compared. The careful comparison of six aspects includes the EIS historical development, their roles, the educational inspectorate organizations (EIO), the standards for selecting and appointing inspectors, the training of inspectors, and the inspection approaches used by the EIOs in China and in the Netherlands. Finally, the implications of this comparison for policy-makers, inspectors, researchers, and practitioners are discussed.
Keywords: inspection